From Racialization to World Citizenship: The Transnationality of Taiwan and the Early Psychiatric Epidemiological Studies of the World Health Organization. Issue 2 (1st June 2016) - Wu, Harry Yi-Jui
Abstract : This article illustrates the exchange of knowledge, sharing of methods, and formation of collaborative research between Taiwan and the World Health Organization (WHO) by discussing a series of large-scale epidemiological studies on mental disorders conducted by the research team of National Taiwan University Hospital in the early postwar years. This article focuses on the purpose, importance, and legacy of the research within Taiwan and in the international social psychiatry projects led by WHO. The author analyzes the active and passive roles that these studies played in the context of postwar decolonization and the short-lived milieu of scientific internationalism aspired by the United Nations and its specialized agencies. WHO's demand to outsource experts from developing countries was due to the lack of sources and enthusiasm of experts from Taiwan to participate in intergovernmental organizations and the self-fashioning of psychiatrists in Taiwan in order to build a national medical discipline that facilitated the connubiality between the two. Moreover, the psychiatric epidemiological research conducted in Taiwan was influenced by the survey-based Japanese ethnological studies developed in the first half of the twentieth century and was designed to build a national medical discipline after World War II. This type of research corresponded to the visions of international scientific communities to deracialize human sciences and fulfill the pursuit of knowledge on the basis of the WHO ideology of "world citizenship." The cultural determinism approach matched the dominant neo-Freudian theories of psychopathology, which depart from the biodeterminism derived from the experiences of colonial psychiatry, and provided the foundation for the universal profiles of mental disorders that WHO mental health experts idealistically attempted to establish.